Experimental assessment of IAQ improvement in naturally ventilated educational buildings - Pinto, Manuel (2014)
Indoor environmental conditions in classrooms, in particular temperature and indoor air quality, influence students’ health, attitude and performance. In recent years several studies regarding indoor environmental quality of classrooms were published and natural ventilation proved to have great potential, particularly in southern European climate. This research aimed to evaluate indoor environmental conditions in 8 schools and to assess their improvement potential by simple natural ventilation strategies. Temperature, relative humidity and carbon dioxide concentration were measured in 32 classrooms. Ventilation performance of the classrooms was deeply characterized by tracer gas measurements of the air change rate assuming different windows related boundary conditions. A total of 110 tracer gas measurements were made. The complete characterization of the classrooms ventilation performance was relevant for the definition of the ventilation protocol since air change rate helped to pinpoint the best ventilation strategy for each case study. The results of the ventilation protocol implementation were very encouraging and, globally, a significant decrease on the CO2 concentration was observed without modifying the comfort conditions. This paper presents and discusses the main conclusions of the measurements campaign performed in the referred classrooms.